2011
DOI: 10.1007/s11250-011-0012-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of vitamins A, E, and C and lipid peroxidation status of breeding and pregnant sheep during dry seasons on medium-to-low quality forages

Abstract: This study assessed the changes of plasma vitamin A, E, and C and the lipid peroxidation status of sheep during breeding and pregnancy under drought conditions. The study was conducted on 105 cross-bred fat tailed ewes, 3-5 years old with body condition scores (BCS) of 2.5 to 3.5. The ewes were grazing on medium-to-low quality forages during summer and low quality forages within the succeeding months and had ad libitum access to a mixture of alfalfa hay (40%) and wheat straw (60%) in the afternoons. From 3 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
6
17
0
1
Order By: Relevance
“…In P and EM groups we found that MDA increased progressively while VitE decreased, indicating rising oxidative stress and presumably high levels of ROS production until 28 d when both parameters plateaued. Similar VitE and MDA trends have been observed in pregnant sheep by Mohebbi-Fani et al (2012) supporting our hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…In P and EM groups we found that MDA increased progressively while VitE decreased, indicating rising oxidative stress and presumably high levels of ROS production until 28 d when both parameters plateaued. Similar VitE and MDA trends have been observed in pregnant sheep by Mohebbi-Fani et al (2012) supporting our hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…The principle of this method consists in the reaction of MDA with thiobarbituric acid in acidic conditions and at a higher temperature to form a pink MDA-(TBA)2 complex (Fig. 2), which can be quantified spectrophotometrically at 532 nm [17,[66][67][68][69][70]. TBARS method measures the amount of MDA generated during lipid peroxidation, however, other aldehydes generated during lipid peroxidation, which also absorb at 532 nm, may react with TBA [71].…”
Section: Tbars Tba-mda Adductsmentioning
confidence: 99%
“…It has been proposed that elevated reproductive effort should increase an animal's vulnerability to oxidative stress [9], [10], [11], and this has been demonstrated in some bird and reptile species [9], [12], [13], [14], [15], [16]. In eutherian mammals, ROS production is elevated, in part, by mitochondrial activity of the placenta[17], [18], and during gestation sows, humans and sheep exhibit an increase in oxidative damage along with a reduction in antioxidant capacity[19], [20], [21], [22], [23](but see[24]). Oxidative damage also increases with number or mass of offspring produced in sheep, mice and Eastern chipmunks ( Tamias striatus ) [25], [26], [27], [28].…”
Section: Introductionmentioning
confidence: 99%